Pembuatan Pupuk Organik Cair (POC) Dari Limbah Ikan Non Target Hasil Tangkapan Nelayan - Monika, Nova Suryawati; Wairara, Stenly Suryani; Sunarni, Sunarni (Universitas Musamus, Merauke, Papua, 2021)
The purpose of this study was to determine the content of N (nitrogen), P (phosphorus) and potassium (K) or NPK in dry waste fish and in liquid organic fertilizer (POC) from non-target fish waste caught by fishermen. The research was conducted in September-November 2020, at the Unmus Merauke Water Resources Management Laboratory and the Unhas Chemistry Laboratory. Sample analysis includes testing the levels of Nitrogen (N), Pospat (P) and Potassium (K) found in non-target fish waste caught by fishermen in Samkai village. The results showed that the NPK analysis results in dry waste fish had levels of Nitrogen (N) 0.58%, Phospor (P) 2.86% and Potassium (K) 0.01%. The results of the analysis of liquid organic fertilizer (POC) from fish waste, while the best analysis of liquid organic fertilizer (POC) on Nitrogen (N) nutrients at P3 was 0.27%, Phospor nutrients at P3 were 1.25% and for Potassium (K) nutrients at P1 equal to 0.74%.